Deformations of the Ear and Their Nonsurgical Correction. (June 2019) - Chang, Catherine S.; Bartlett, Scott P.
The incidence of congenital ear deformities has been documented to be as high as 58% of all newborns. Unfortunately, the majority of these deformations do not spontaneously self-correct, leaving the child with a permanent deformity that can only be corrected through surgery. With the evolving simplicity of ear molding that can be done in the office, this can obviate the need for unnecessary surgery that comes with its own set of complications and a higher cost. Early detection and early treatment is key for successful ear molding. The purpose of this article is to review the types of deformational ear deformities and the most up-to-date literature on ear molding, increase awareness to this topic, and ultimately increase patient and parental satisfaction with their overall care.